Common coupled fixed point theorems for θ-ψ-contraction mappings endowed with a directed graph - Suthep Suantai (2018)
© 2015, Suantai et al. In this paper, we present some existence and uniqueness results for coupled coincidence point and common fixed point of θ-ψ-contraction mappings in complete metric spaces endowed with a directed graph. Our results generalize the results obtained by Kadelburg et al. (Fixed Point Theory Appl. 2015:27, 2015, doi:10.1007/s11590-013-0708-4). We also have an application to some integral system to support the results.